Control interno y el proceso de recaudación en el área de rentas de la Municipalidad Provincial de Ucayali 2022 - Namay Reyes, Alejandro Eladio (2022)
The general objective of the research was to determine the relationship between internal control and the collection process in the Revenue Area of the Provincial Municipality of Ucayali, 2022, where an applied type study, correlational level and non-experimental design was chosen, consisting of for a population of 14 workers. The same ones that were surveyed through the survey technique, using a questionnaire of questions. The work concluded that internal control is qualified as regular (29%), because the institution never establishes the ethical values that must be respected in the IC process, and that sometimes they establish the necessary changes to counteract the risks, but always they prepare manuals and/or process diagrams of the control activities, since the information is never communicated internally, and sometimes they carry out permanent evaluation of the procedural processes. For its part, the collection process is qualified as regular (29%), since sometimes the institution determines the taxpayer's tax obligations, and almost always the institution forms a unit that is responsible for carrying out collections. In the same way, it was determined that the internal control is significantly related to the collection process with a coefficient of 0.920 Pearson, likewise, it was established so that the control environment contrasts with a coefficient of 0.850; for risk assessment a coefficient of 0.793; control activities a coefficient of 0.855; information/communication a coefficient of 0.719; and supervision/monitoring a coefficient of 0.831, each of which is significantly related to the collection process.